Lasers semicondutores sob injeção ótica ortogonalmente polarizada - Oliveira, Abinael de brito (2014)
Here we present a systematic analysis of the dynamics in the frequency of semiconductor lasers in systems under orthogonal optical feedback or external injection, with and without frequency discriminator. We measure the parameter of proportionality between the change of frequency and the power level of the orthogonally polarized light injected into the cavity. We perform an application of this injection technique for frequency sweep that allows varying the frequency in a range of tens of GHz and apply it in an experience of spectroscopy. This technique allows frequency sweep without changing the main laser power, which is fed by another, control laser, whose wavelength is di erent from the principal. We have analyzed the dynamics of the semiconductor laser frequency subject to orthogonal optical feedback and injection in a con guration where a di raction grating works as a spectral lter. Using a di raction grating as frequency discriminator in these systems, we observe a dynamical behavior in the laser emission frequency.